High-salt-spray-corrosion-resistant thick copper packaging circuit board and preparation method thereof

By building a multi-layer collaborative protection system on thick copper packaged circuit boards, the structural failure problem of thick copper packaged circuit boards in high salt spray and high temperature environments is solved, higher corrosion resistance and service life are achieved, and the stability of mass production is improved.

CN120751578AActive Publication Date: 2025-10-03HUIZHOU RUNZHONG TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511179692.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-22
Publication Date
2025-10-03
Estimated Expiration
2045-08-22

AI Technical Summary

Technical Problem

Existing thick copper packaged circuit boards are prone to structural failures such as delamination and cracking in high salt fog and high temperature environments. Traditional packaging coatings and anti-corrosion film layers have insufficient adhesion and are unable to provide long-lasting barrier protection.

Method used

A multi-layer synergistic protection system using a glass fiber-BT resin composite core layer, a thick copper conductor layer, a fluorine-modified polyimide encapsulation layer and a surface anti-corrosion composite coating is formed through hot melt impregnation, hot pressing lamination, spraying and thermal curing processes to form multi-layer synergistic protection, thereby enhancing interface stability and corrosion resistance.

Benefits of technology

It significantly improves the corrosion resistance of circuit boards in high salt fog and high humidity and heat environments, enhances structural integrity and service life, solves the problems of weak interface adhesion and uneven film formation, and improves mass production stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120751578A_ABST
    Figure CN120751578A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electronic packaging materials, in particular to a high-salt-spray-corrosion-resistant thick copper packaging circuit board and a preparation method thereof, and the method comprises the following steps: S1, preparing a glass fiber-BT resin composite core layer for later use; s2, preparing fluorine-modified polyimide packaging coating liquid for later use; s3, preparing a surface anti-corrosion composite coating and an anti-corrosion composite coating for later use; s4, the thick copper foil is attached to the glass fiber-BT composite core layer, and a thick copper conductor is obtained; s5, the surface of the thick copper conductor layer is coated with the fluorine-modified polyimide packaging coating liquid to form a packaging layer; s6, anti-corrosion paint is sprayed on the surface of the packaging layer, and a composite anti-corrosion coating is formed; and S7, carrying out integral curing and hot-pressing leveling, and finally obtaining a finished product of the thick copper packaging circuit board. According to the method, the corrosion resistance and the structural stability of the thick copper circuit board in a high-salt-spray environment are remarkably improved by constructing a multi-layer collaborative protection structure and optimizing the preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic packaging materials, and in particular to a thick copper packaging circuit board resistant to high salt spray corrosion and a preparation method thereof. Background Art

[0002] In high-load scenarios such as high-power electronics, electric vehicles, and power conversion equipment, circuit boards bear the dual functional requirements of large current and high-density wiring. Thick copper packaged circuit boards are widely used in the above-mentioned fields due to their excellent electrical conductivity and heat load capacity. However, as their application environment expands to extreme conditions such as high humidity, high salt spray, and high temperature, the long-term service reliability of circuit boards is facing severe challenges. In order to cope with the continuous erosion of external corrosive media, the industry has gradually introduced packaging coatings, anti-corrosion coatings, and structural modification methods to extend the service life of circuit boards and stabilize their performance output.

[0003] However, existing packaging and protection solutions still have significant shortcomings. On the one hand, conventional thick copper sheets have weak interlayer bonding interfaces, making them prone to structural failures such as delamination and cracking over long-term use. On the other hand, traditional packaging coatings and anti-corrosion films are mostly single-component or have low adhesion, making them difficult to provide long-term barrier protection in high-salt fog environments. Therefore, a thick copper packaging circuit board resistant to high-salt fog corrosion and a preparation method are urgently needed to address these issues. Summary of the Invention

[0004] Based on the above objectives, the present invention provides a thick copper packaged circuit board resistant to high salt spray corrosion and a preparation method thereof.

[0005] A thick copper packaged circuit board resistant to high salt spray corrosion comprises a glass fiber-BT resin composite core layer, a thick copper conductor layer, a fluorine-modified polyimide packaging layer and a surface anti-corrosion composite coating.

[0006] Optionally, the fluorine-modified polyimide encapsulation layer is composed of the following raw materials in percentage by mass: Fluorinated polyimide resin accounts for 65-75%; Nano-alumina accounts for 8-12%; Polytetrafluoroethylene powder accounts for 3-6%; γ-aminopropyltriethoxysilane accounts for 1-2%, The balance is a mixed solvent of toluene and NMP; The surface anti-corrosion composite coating is composed of the following components by mass percentage: Silane coupling agents account for 25-35%; Organic zirconium salts account for 30-40%; Polyvinyl butyral accounts for 8-15%; Antioxidant 1010 accounts for 5-10%, The balance was xylene.

[0007] A method for preparing a thick copper packaged circuit board resistant to high salt spray corrosion comprises the following steps: S1: premixing BT resin and glass fiber cloth in a predetermined ratio, and adopting hot melt impregnation and pressing process to prepare a glass fiber-BT composite core layer for standby use; S2: preparing a fluorine-modified polyimide encapsulation layer material by sequentially adding a fluorinated polyimide resin, nano-alumina, polytetrafluoroethylene powder, and a silane coupling agent into a mixed solvent of toluene and NMP, and uniformly dispersing them under stirring to form an encapsulation coating solution for use; S3: preparing a surface anti-corrosion composite coating material, adding a silane coupling agent, an organic zirconium salt, polyvinyl butyral and an antioxidant 1010 to a xylene solvent in sequence, and stirring evenly to form an anti-corrosion composite coating for later use; S4: The roughened thick copper foil is laminated to the glass fiber-BT composite core layer prepared in S1 by hot pressing to obtain a thick copper conductor; S5: evenly applying the fluorine-modified polyimide encapsulation coating liquid prepared in S2 to the surface of the thick copper conductor layer, drying and thermally curing to form an encapsulation layer; S6: applying the anti-corrosion coating prepared in S3 to the surface of the encapsulation layer in sequence by spraying to form a composite anti-corrosion coating; S7: The circuit board with each layer of construction is solidified and hot-pressed at a preset temperature to obtain a finished thick copper packaged circuit board.

[0008] Optionally, the S1 specifically includes: S11: evenly spreading BT resin on the surface of the spread glass fiber cloth to form a resin covering layer, wherein the mass ratio of the BT resin powder to the glass fiber cloth is 6:4; S12: feeding the resin-covered glass fiber cloth into a hot melt impregnation device and heating it at a temperature of 180°C to 200°C, so that the BT resin melts and penetrates into the gaps between the fibers under heating, forming a semi-cured sheet in a fully resin-impregnated state; S13: hot pressing and curing the semi-cured sheet in a pressing device under the conditions of a pressure of 0.8 to 1.2 MPa, a temperature of 200° C. to 220° C., and a time of 90 to 120 seconds to obtain a glass fiber-BT composite core layer with a thickness of 0.2 mm to 0.4 mm.

[0009] Optionally, the S2 specifically includes: S21: In a stirred reactor, toluene and NMP are mixed in a mass ratio of 3:2 to prepare a mixed solvent, and the mixed solvent is heated to 40° C. for later use; S22: adding the fluorinated polyimide resin to the heated solvent, maintaining a stirring rate of 600-800 rpm, and pre-dissolving the resin at a constant temperature for 20-30 minutes to form a preliminary sol state; S23: Add nano-alumina, polytetrafluoroethylene powder and γ-aminopropyltriethoxysilane in sequence, increase the stirring rate to 900-1000 rpm, and continue dispersing at 60°C for 50-60 minutes to form a homogeneous suspension system; S24: After the dispersion is completed, the mixture is allowed to stand for degassing for 30 minutes to obtain a fluorine-modified polyimide encapsulation coating liquid.

[0010] Optionally, the S3 specifically includes: S31: Add xylene solvent to the stirred reaction vessel, control the initial temperature to 25°C-30°C, and set the stirring rate to 500-600 rpm; S32: Add silane coupling agent and organic zirconium salt in sequence, and continue stirring for 20-30 minutes; S33: Then, polyvinyl butyral and antioxidant 1010 were added, and the stirring rate was increased to 800-900 rpm. Stirring was continued at 40° C.-50° C. for 30-40 minutes to form a composite solution; S34: Filter the composite solution through 100 meshes to remove undissolved particles to obtain an anti-corrosion composite coating.

[0011] Optionally, the S4 specifically includes: S41: roughening an electrolytic copper foil having a thickness of 200-400 μm using a chemical micro-etching solution, controlling the rough etching time to be 30-60 seconds, and achieving a surface roughness Ra of 0.8-1.5 μm after the treatment; S42: Cleaning the roughened copper foil surface with deionized water and performing hot air drying at 80° C. to 100° C. to remove residual liquid and moisture on the surface; S43: The glass fiber-BT composite core layer prepared in S1 is laminated with the roughened copper foil in a hot press. The pressing temperature is set to 190°C-210°C, the pressure is set to 1.0-1.5 MPa, and the holding time is set to 120-180 seconds. After cooling to room temperature, a thick copper conductor structure with a stable combination of the copper foil and the core layer is formed.

[0012] Optionally, the S5 specifically includes: S51: applying the fluorine-modified polyimide encapsulation coating liquid prepared in S2 to the surface of the thick copper conductor layer through a coating machine, controlling the application speed to be 200-300 mm / s; S52: Send the coated circuit board into a hot air drying oven, set the drying temperature to 80℃-100℃, and the drying time to 5-10 minutes to remove the solvent residue and initially set the coating film; S53: placing the dried sample in a hot press furnace for heat curing treatment, setting the curing temperature to 220° C.-250° C. and the heat preservation time to 30-40 minutes, to form a cured encapsulation layer with a thickness of 15-20 μm.

[0013] Optionally, the S6 specifically includes: S61: evenly spraying the anti-corrosion composite coating prepared in S3 onto the surface of the fluorine-modified polyimide encapsulation layer, with the nozzle diameter set to 0.3-0.5 mm, the spraying pressure controlled at 0.2-0.3 MPa, the spraying distance set to 150-200 mm, and the entire surface covered in a spiral trajectory to form a first coating layer with an initial film thickness controlled at 4-6 μm; S62: After the first spraying is completed, hot air pre-drying is performed at 70℃-80℃ for 5-8 minutes; S63: Repeat the second spraying process, with the application track staggered with the first, and control the coating thickness to be 3-5 μm. After completion, repeat the drying step of S62 again to form a composite anti-corrosion coating with a final film thickness of 7-11 μm; S64: Place the sprayed circuit board in a 50-60°C environment for curing for 2-3 hours.

[0014] Optionally, the S7 specifically includes: S71: Place the printed circuit board sprayed in S6 on a constant temperature hot pressing platform, set the initial heating rate to 2-3°C / min, and gradually increase the temperature to 150-160°C; S72: When the temperature stabilizes, apply constant hot pressing, control the pressure at 0.5-0.8 MPa, and maintain the hot pressing time for 30-40 minutes; S73: After the hot pressing is completed, the circuit board is slowly cooled to room temperature without removing the pressure, and the cooling rate is controlled at 1-2°C / min. After the temperature is lower than 40°C, the pressure is released and the board is removed to obtain a finished thick copper packaged circuit board.

[0015] Beneficial effects of the present invention: The present invention forms a multi-layer synergistic protection system by sequentially constructing a fluorine-modified polyimide encapsulation layer and a multi-component composite anti-corrosion coating on the outside of a thick copper conductor structure, thereby significantly enhancing the corrosion resistance of the circuit board in high salt fog and high humidity and heat environments. Among them, the fluorinated polyimide and the nanofiller synergistically construct a hermetic encapsulation film layer with excellent insulation and interface stability. The anti-corrosion coating adopts a compound design of silane, organic zirconium salt and polymer film-forming agent, which can effectively block corrosive media and improve the surface resistance to chemical erosion.

[0016] The present invention prepares the encapsulation and anti-corrosion coating liquid in situ and adopts a staged coating, thermal curing and hot pressing leveling process to achieve synchronous thermal curing, stress coordination and interface stability for each structural layer of the circuit board. This effectively solves the problems of weak interface adhesion, uneven film formation and dimensional deformation in traditional processes, thereby significantly improving the structural integrity, service life and mass production stability of thick copper circuit boards. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0018] Figure 1 Schematic diagram of a method for preparing a thick copper packaged circuit board according to an embodiment of the present invention. DETAILED DESCRIPTION

[0019] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments. It is also noted that, to provide a more detailed description, the following embodiments are best and preferred embodiments, and those skilled in the art may employ alternative methods for implementing certain known technologies. Furthermore, the accompanying drawings are intended only to provide a more detailed description of the embodiments and are not intended to limit the present invention.

[0020] It should be noted that references in the specification to "one embodiment," "an embodiment," "exemplary embodiments," "some embodiments," etc. indicate that the described embodiments may include specific features, structures, or characteristics, but not necessarily every embodiment will include such specific features, structures, or characteristics. Furthermore, when specific features, structures, or characteristics are described in conjunction with an embodiment, it is within the knowledge of persons skilled in the relevant art to implement such features, structures, or characteristics in conjunction with other embodiments (whether or not explicitly described).

[0021] In general, terms can be understood, at least in part, from their use in context. For example, depending at least in part on the context, the term "one or more" as used herein can be used to describe any feature, structure, or characteristic in the singular sense, or can be used to describe a combination of features, structures, or characteristics in the plural sense. Additionally, the term "based on" can be understood as not necessarily intended to convey an exclusive set of factors, but can instead, depending at least in part on the context, allow for the presence of other factors that are not necessarily explicitly described.

[0022] Example 1 A thick copper packaged circuit board resistant to high salt spray corrosion comprises a glass fiber-BT resin composite core layer, a thick copper conductor layer, a fluorine-modified polyimide packaging layer and a surface anti-corrosion composite coating.

[0023] The fluorine-modified polyimide encapsulation layer is composed of the following raw materials by mass percentage: Fluorinated polyimide resin accounts for 78%; Nano-alumina accounts for 10%; Polytetrafluoroethylene powder accounts for 5%; γ-aminopropyltriethoxysilane accounts for 1.5%, The balance is a mixed solvent of toluene and NMP; The surface anti-corrosion composite coating is composed of the following components by mass percentage: Silane coupling agents account for 30%; Organic zirconium salts account for 35%; Polyvinyl butyral accounts for 10%; Antioxidant 1010 accounts for 7%; The balance was xylene.

[0024] like Figure 1 As shown, a method for preparing a thick copper packaged circuit board resistant to high salt spray corrosion comprises the following steps: S1: premixing BT resin and glass fiber cloth in a predetermined ratio, and adopting hot melt impregnation and pressing process to prepare a glass fiber-BT composite core layer for standby use; S2: preparing a fluorine-modified polyimide encapsulation layer material by sequentially adding a fluorinated polyimide resin, nano-alumina, polytetrafluoroethylene powder, and a silane coupling agent into a mixed solvent of toluene and NMP, and uniformly dispersing them under stirring to form an encapsulation coating solution for use; S3: preparing a surface anti-corrosion composite coating material, adding a silane coupling agent, an organic zirconium salt, polyvinyl butyral and an antioxidant 1010 to a xylene solvent in sequence, and stirring evenly to form an anti-corrosion composite coating for later use; S4: The roughened thick copper foil is laminated to the glass fiber-BT composite core layer prepared in S1 by hot pressing to obtain a thick copper conductor; S5: evenly applying the fluorine-modified polyimide encapsulation coating liquid prepared in S2 to the surface of the thick copper conductor layer, drying and thermally curing to form an encapsulation layer; S6: applying the anti-corrosion coating prepared in S3 to the surface of the encapsulation layer in sequence by spraying to form a composite anti-corrosion coating; S7: The circuit board with each layer of construction is solidified and hot-pressed at a preset temperature to obtain a finished thick copper packaged circuit board.

[0025] S1 specifically includes: S11: evenly spreading BT resin on the surface of the spread glass fiber cloth to form a resin covering layer, wherein the mass ratio of BT resin powder to glass fiber cloth is 6:4; S12: feeding the resin-covered glass fiber cloth into a hot melt impregnation device and heating it at 190°C to melt the BT resin and penetrate into the gaps between the fibers, forming a prepreg sheet fully impregnated with the resin; S13: The semi-cured sheet is hot-pressed and cured in a pressing device at a pressure of 1.0 MPa, a temperature of 210°C, and a time of 100 seconds to obtain a glass fiber-BT composite core layer with a thickness of 0.3 mm. The above steps can ensure the uniform distribution of the resin inside the fiber, forming a core layer with a dense structure and stable dielectric properties, which helps to improve the interface bonding strength of the subsequent copper layer and the overall thermal stability and mechanical strength of the circuit board.

[0026] S2 specifically includes: S21: In a stirred reactor, toluene and NMP are mixed in a mass ratio of 3:2 to prepare a mixed solvent, and the mixed solvent is heated to 40° C. for later use; S22: adding the fluorinated polyimide resin to the heated solvent, maintaining a stirring rate of 700 rpm, and pre-dissolving the resin at a constant temperature for 25 minutes to form a preliminary sol state; S23: Nano-alumina, polytetrafluoroethylene powder, and γ-aminopropyltriethoxysilane were added in sequence, and the stirring rate was increased to 950 rpm. The dispersion was continued at 60°C for 55 minutes to form a homogeneous suspension system. S24: After the dispersion is completed, the mixture is allowed to stand and degas for 30 minutes to obtain a fluorine-modified polyimide encapsulation coating liquid. The above steps can effectively improve the interfacial compatibility between the nanofiller and the resin system by controlling the order of raw material addition and the dispersion temperature conditions, avoid particle agglomeration, and ensure that the encapsulation coating liquid has good leveling and uniform film formation during the subsequent application process, thereby providing a basis for forming a dense and uniform high-performance encapsulation layer.

[0027] S3 specifically includes: S31: Add xylene solvent to the stirred reaction vessel, control the initial temperature to 27°C, and set the stirring rate to 550 rpm; S32: Add silane coupling agent and organic zirconium salt in sequence, and continue stirring for 25 minutes to ensure that the zirconium-based complex and silane are evenly dissolved; S33: Then, polyvinyl butyral and antioxidant 1010 were added, and the stirring rate was increased to 850 rpm. Stirring was continued at 45° C. for 35 minutes to form a composite solution. S34: Filter the composite solution through 100 mesh to remove undissolved particles to obtain an anti-corrosion composite coating; the above steps can improve the dissolution efficiency of organic zirconium salts and silane materials in the solvent system by controlling the addition order of different components and the stirring temperature range, avoid reaction side polymerization or pre-crosslinking problems, and ensure uniform distribution of polyvinyl butyral and antioxidant, thereby obtaining an anti-corrosion composite coating with strong interface bonding, good coating continuity and storage stability, which meets the subsequent uniform spraying and film formation requirements.

[0028] S4 specifically includes: S41: roughening an electrolytic copper foil having a thickness of 300 μm using a chemical micro-etching solution, controlling the roughening time to be 40 seconds, and achieving a surface roughness Ra of 1.0 μm after the treatment; S42: Cleaning the roughened copper foil surface with deionized water and performing hot air drying at 90° C. to remove residual liquid and moisture on the surface; S43: The glass fiber-BT composite core layer prepared in S1 is laminated with the roughened copper foil in a hot press. The pressing temperature is set to 200°C, the pressure is set to 1.2 MPa, and the holding time is set to 160 seconds. After cooling to room temperature, a thick copper conductor structure with a stable combination of the copper foil and the core layer is formed. By roughening the surface of the copper foil before hot pressing, the actual contact area between the copper foil and the BT resin-based core layer can be significantly increased. Combined with the reasonable control of the subsequent hot pressing parameters, a strong mechanical locking structure is ensured at the copper-resin interface, thereby improving the adhesion stability of the conductor layer.

[0029] S5 specifically includes: S51: applying the fluorine-modified polyimide encapsulation coating liquid prepared in S2 to the surface of the thick copper conductor layer by a coating machine, controlling the coating speed to 250 mm / s, and adopting a cross-bidirectional coating method to ensure uniform and complete coverage of the surface; S52: The coated circuit board is sent to a hot air drying oven, and the drying temperature is set to 90°C for 8 minutes to remove the solvent residue and initially set the coating film; S53: The dried sample is placed in a hot press for heat curing treatment. The curing temperature is set to 230°C and the holding time is 35 minutes to form a cured encapsulation layer with a thickness of 18μm. By controlling the coating thickness and application path, the encapsulation liquid forms a continuous and uniform film layer on the surface of the copper conductor. Then, through segmented drying and high-temperature heat curing, the fluorine-modified polyimide is fully cross-linked to form a film, enhancing the interfacial adhesion and heat resistance stability of the encapsulation layer, thereby providing excellent barrier protection performance for the circuit board in a high salt fog environment.

[0030] S6 specifically includes: S61: The anti-corrosion composite coating prepared in S3 is evenly sprayed on the surface of the fluorine-modified polyimide encapsulation layer. The nozzle diameter is set to 0.4 mm, the spraying pressure is controlled at 0.25 MPa, the spraying distance is 180 mm, and the entire surface is covered in a spiral trajectory to form a first coating. The initial film thickness is controlled at 5 μm. S62: After the first coat of spraying is completed, hot air pre-drying is performed at 75°C for 7 minutes to ensure stable adhesion of the first coat of coating; S63: Repeat the second spraying process, with the application track staggered with the first, and control the coating thickness to 4 μm. After completion, repeat the drying step of S62 again to form a composite anti-corrosion coating with a final film thickness of 9 μm; S64: The sprayed circuit board is placed in a static curing environment at 55°C for 2.5 hours to improve the coating structure stability and complete solvent evaporation; through two staggered spraying and staged pre-drying treatment, the various anti-corrosion components are orderly distributed in the multi-layer coating to form a stable laminated structure; combined with the static curing step, it is ensured that the coating is fully set and the component reaction is completed, thereby obtaining a composite protective coating with strong adhesion and long-lasting salt spray resistance, thereby enhancing the overall resistance of the circuit board to chemical corrosion.

[0031] S7 specifically includes: S71: Place the printed circuit board sprayed in S6 on a constant temperature hot pressing platform, set the initial heating rate to 2.5°C / min, and gradually increase the temperature to 155°C; S72: When the temperature stabilizes, applying constant hot pressing with the pressure controlled at 0.6 MPa for 35 minutes to achieve thermal curing of the interfaces of the layers and release of internal stress; S73: After the hot pressing is completed, the circuit board is slowly cooled to room temperature without removing the pressure, and the cooling rate is controlled at 1.5℃ / min. After the temperature is lower than 40℃, the pressure is released and the board is removed to obtain the finished thick copper packaged circuit board. By setting the gentle heating and slow cooling curves, and combining the medium pressure hot pressing holding time, the core layer resin, packaging coating and anti-corrosion film layer can be effectively cured simultaneously, thereby improving the interface bonding strength and overall flatness of the multi-layer structure.

[0032] Example 2 The encapsulation layer formula is: 65% fluorinated polyimide resin, 8% nano-alumina, 3% polytetrafluoroethylene powder, 1% γ-aminopropyltriethoxysilane, and the balance is a mixed solvent of toluene and NMP.

[0033] Anti-corrosion coating formula: 25% silane coupling agent, 30% organic zirconium salt, 8% polyvinyl butyral, 5% antioxidant 1010, and the balance is xylene.

[0034] The preparation steps are as follows: S1: BT resin and glass fiber cloth were premixed in a mass ratio of 6:4, and the BT resin was evenly spread on the surface of the spread glass fiber cloth. The cloth was then sent to a 180°C heating zone for hot melt impregnation, allowing the BT resin to fully penetrate the fiber gaps to form a prepreg sheet. The prepreg sheet was hot pressed at 200°C and 0.8 MPa for 90 seconds to obtain a glass fiber-BT composite core layer with a thickness of 0.2 mm. S2: Toluene and NMP were mixed in a stirring vessel at a mass ratio of 3:2 and heated to 40°C; fluorinated polyimide resin was first added and dissolved at a stirring rate of 600 rpm for 20 minutes to form a preliminary sol; nano-alumina, polytetrafluoroethylene powder, and γ-aminopropyltriethoxysilane were then added in sequence, and the stirring was increased to 900 rpm. The mixture was dispersed at 60°C for 50 minutes and allowed to stand for 30 minutes for degassing to obtain an encapsulation coating solution; S3: Add xylene to the reactor, set the temperature to 25°C, and control the stirring rate at 500 rpm; add a silane coupling agent and an organic zirconium salt in sequence, stir for 20 minutes, then add polyvinyl butyral and antioxidant 1010, increase the stirring rate to 800 rpm and raise the temperature to 40°C, continue stirring for 30 minutes, and finally filter through a 100-mesh filter to remove impurities to obtain an anti-corrosion composite coating; S4: A 200μm thick electrolytic copper foil was roughened using a chemical microetching solution for 30 seconds, with a surface roughness Ra of 0.8μm. The foil was then rinsed with deionized water and dried under 80°C hot air. The treated copper foil and the core layer prepared in S1 were hot pressed at 190°C and 1.0MPa for 120 seconds, followed by cooling to form a thick copper conductor structure. S5: The encapsulation coating liquid is evenly applied to the surface of the copper conductor using a coating machine at a speed of 200 mm / s; the conductor is then dried in an 80°C hot air oven for 5 minutes to remove the solvent; the conductor is then heat-cured in a hot press at 220°C for 30 minutes to form a cured encapsulation layer with a thickness of 15 μm; S6: Using a 0.3mm nozzle, 0.2MPa air pressure, and a spray distance of 150mm, the first coat was sprayed in a spiral pattern to a film thickness of 4μm. This was followed by hot air drying at 70°C for 5 minutes. A second coat was applied with staggered trajectories to a film thickness of 3μm. The drying process was repeated to a final film thickness of 7μm. The coated panels were left to cure at 50°C for 2 hours. S7: Place the circuit board on a constant temperature hot pressing platform with a heating rate of 2°C / min. After heating to 150°C, apply a constant pressure of 0.5MPa and maintain for 30 minutes. After completion, cool down to 40°C without removing the pressure, and control the cooling rate at 1°C / min. Release the pressure and take out the circuit board to obtain the final product.

[0035] Example 3 The encapsulation layer formula is: 75% fluorinated polyimide resin, 12% nano-alumina, 6% polytetrafluoroethylene powder, 2% γ-aminopropyltriethoxysilane, and the balance is a mixed solvent of toluene and NMP.

[0036] Anti-corrosion coating formula: 35% silane coupling agent, 40% organic zirconium salt, 15% polyvinyl butyral, 10% antioxidant 1010, and the balance is xylene.

[0037] The preparation steps are as follows: S1: BT resin and glass fiber cloth were premixed in a mass ratio of 6:4, and the BT resin was evenly spread on the surface of the spread glass fiber cloth. The cloth was then sent to a 200°C heating zone for hot melt impregnation, allowing the BT resin to fully penetrate the gaps between the fibers to form a prepreg sheet. The prepreg sheet was hot pressed at 220°C and 1.2 MPa for 120 seconds to obtain a glass fiber-BT composite core layer with a thickness of 0.4 mm. S2: Toluene and NMP were mixed in a stirring vessel at a mass ratio of 3:2 and heated to 40°C; fluorinated polyimide resin was first added and dissolved at a stirring rate of 800 rpm for 30 minutes to form a preliminary sol; nano-alumina, polytetrafluoroethylene powder, and γ-aminopropyltriethoxysilane were then added in sequence, and the stirring was increased to 1000 rpm. The mixture was dispersed at 60°C for 60 minutes and allowed to stand for 30 minutes for degassing to obtain an encapsulation coating solution; S3: Add xylene to the reactor, set the temperature to 30°C, and control the stirring rate at 600 rpm; add a silane coupling agent and an organic zirconium salt in sequence, stir for 30 minutes, then add polyvinyl butyral and antioxidant 1010, increase the stirring rate to 900 rpm and raise the temperature to 50°C, continue stirring for 40 minutes, and finally filter through a 100-mesh filter to remove impurities to obtain an anti-corrosion composite coating; S4: A 400μm thick electrolytic copper foil was roughened using a chemical microetching solution for 60 seconds, with a surface roughness Ra of 1.5μm. The foil was then rinsed with deionized water and dried in hot air at 100°C. The treated copper foil and the core layer prepared in S1 were hot pressed at 210°C and 1.5MPa for 180 seconds, followed by cooling to form a thick copper conductor structure. S5: The encapsulation coating liquid is evenly applied to the surface of the copper conductor using a coating machine at a speed of 300 mm / s; the conductor is dried in a hot air oven at 100°C for 10 minutes to remove the solvent; the conductor is then heat-cured in a hot press at 250°C for 40 minutes to form a cured encapsulation layer with a thickness of 20 μm; S6: Using a 0.5mm nozzle, 0.3MPa air pressure, and a spray distance of 200mm, the first coat was sprayed in a spiral pattern to a film thickness of 6μm. This was followed by hot air drying at 80°C for 8 minutes. A second coat was applied with staggered trajectories to a film thickness of 5μm. The drying process was repeated to a final film thickness of 11μm. The coated panels were then allowed to cure at 60°C for 3 hours. S7: Place the circuit board on a constant temperature hot pressing platform with a heating rate of 3°C / min. After heating to 160°C, apply a constant pressure of 0.8MPa and maintain for 40 minutes. After completion, cool down to 40°C without removing the pressure, and control the cooling rate at 2°C / min. Release the pressure and take out the circuit board to obtain the final product.

[0038] Comparative Example 1 Step 1: BT resin is impregnated into glass fiber cloth and then dried to form a semi-cured sheet. The semi-cured sheet is then hot-pressed with a 200 μm thick electrolytic copper foil at a temperature of 180°C, a pressure of 1.0 MPa, and a pressing time of 90 seconds to obtain a copper foil-clad substrate. Step 2: Use alkaline etching solution to transfer and etch the copper foil surface, controlling the etching depth to about 50μm to obtain the circuit structure; then rinse the residual liquid with 80℃ pure water and dry it with hot air; Step 3: Evenly spray conventional acrylic conformal paint on the surface of the circuit board. The coating thickness is controlled at 3-5 μm. Dry at 80°C for 10 minutes to obtain the finished product.

[0039] Table 1 Comparison of finished product performance parameters Performance Project unit Example 1 Example 2 Example 3 Comparative Example 1 Thermal decomposition temperature of the encapsulation layer ℃ 465 452 470 380 Surface protective coating adhesion (100-grid test) class 0 1 0 3 Salt spray corrosion blistering time (5% NaCl, 35°C) h ≥1000 800 950 ≤120 Insulation resistance GΩ 10.5 9.2 10.1 4.6 Surface conductivity (after wet heat) μS / cm 0.08 0.1 0.09 0.25 Conductor layer peeling strength N / cm 1.6 1.45 1.52 1.1 Dielectric strength of packaging layer kV / mm 35 30 34 21 Line width retention (after high temperature aging) % 98.7 96.5 97.8 88.4 Thermal shock cycle life (-40~+125℃) Second-rate ≥600 450 550 120 As can be seen from Table 1 above, Example 1 is the best in terms of thermal stability. Its fluorinated polyimide ratio is high and fully dispersed, and the resulting encapsulation layer has a heat-resistant decomposition temperature of 465°C, which is better than other solutions. It also has the highest dielectric strength (35 kV / mm), ensuring electrical safety performance under high temperatures. The corrosion-free blistering time of Example 1 in a 5% NaCl environment exceeds 1000 hours, which is much longer than the 120 hours of Comparative Example 1, indicating that its composite anti-corrosion coating is more effective in thickness, density, and hydrophilic interface inhibition. The conductor layer peel strength and encapsulation layer adhesion are both better than those of conventional solutions. The multi-component fluorine-modified encapsulation layer of Example 1 provides stronger mechanical bonding, ensuring that the circuit board will not delaminate during long-term use. Example 1 has the best comprehensive performance in electrical insulation performance and hot and cold cycle life, reflecting that its overall structural stability is strong and its ability to adapt to extreme environmental changes is better than that of Examples 2 and 3. Comparative Example 1, as a representative of conventional technology, performs worst in almost all performance indicators and cannot meet the requirements of high reliability and high corrosion environment applications. Example 1 is superior to other examples and comparative example 1 in terms of high-temperature insulation, corrosion resistance and interface adhesion performance, and is the most suitable preparation solution for thick copper packaged circuit boards in high salt spray and high temperature complex environments.

[0040] Table 2 Comparison of other performance parameters Comparison Project unit Example 1 Example 2 Example 3 Comparative Example 1 Surface roughness Ra of encapsulation layer (after curing) μm 0.35 0.42 0.4 0.75 Thermal expansion coefficient (Z-axis direction) ppm / ℃ 28 31 29 45 Coating thickness uniformity (standard deviation) μm ±0.4 ±0.7 ±0.6 ±1.2 Copper-package interface shear strength MPa 27.5 24.3 26.1 18.6 Circuit board warpage (after hot pressing) mm / m 0.3 0.6 0.4 1.2 Process residue rate (deposition residue of non-soluble components) % 0.2 0.4 0.3 1.1 First pass rate of board making % 98.8 95.3 97.2 87.5 As shown in Table 2, Example 1 has the lowest surface roughness (0.35 μm) and the smallest coating thickness standard deviation (±0.4 μm), indicating that its coating liquid composition ratio and dispersion process are more reasonable, resulting in a denser and more uniform coating, which is beneficial for electrical insulation and subsequent graphic processing. The thermal expansion coefficient is only 28 ppm / °C, far better than the 45 ppm / °C of Comparative Example 1, which can effectively reduce the risks of warping, cracking, and conductor deformation caused by thermal shock and improve heat-resistant dimensional stability. The interfacial shear strength reaches 27.5 MPa, far higher than the 18.6 MPa of Comparative Example 1, demonstrating the strong adhesion between the encapsulation layer and the copper conductor, ensuring that the encapsulation structure does not peel under high humidity and heat conditions. The overall warpage of the circuit board is only 0.3 mm / m, significantly better than the comparative example, meeting the requirements of high-density component assembly and large board sizes. The first-time pass rate of board production reaches 98.8%, demonstrating strong process control capabilities and greater stability and economy in mass production. In summary, Example 1 demonstrates optimal process adaptability in terms of packaging layer uniformity, dimensional stability, and interface bonding strength, and is a preferred solution for ensuring high reliability and high batch consistency of thick copper packaged circuit boards.

[0041] The present invention encompasses any alternatives, modifications, equivalents, and solutions that fall within the spirit and scope of the present invention. To provide a thorough understanding of the present invention, specific details are described in detail below in connection with the preferred embodiments of the present invention, but those skilled in the art will be able to fully understand the present invention without these detailed descriptions. Furthermore, to avoid unnecessary confusion regarding the essence of the present invention, well-known methods, processes, procedures, components, and circuits have not been described in detail.

[0042] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A thick copper packaged circuit board resistant to high salt spray corrosion, characterized in that: It includes a glass fiber-BT resin composite core layer, a thick copper conductor layer, a fluorine-modified polyimide encapsulation layer, and a surface anti-corrosion composite coating; The fluorine-modified polyimide encapsulation layer is composed of the following raw materials in percentage by mass: Fluorinated polyimide resin accounts for 65-75%; Nano-alumina accounts for 8-12%; Polytetrafluoroethylene powder accounts for 3-6%; γ-aminopropyltriethoxysilane accounts for 1-2%, The balance is a mixed solvent of toluene and NMP; The surface anti-corrosion composite coating is composed of the following components by mass percentage: Silane coupling agents account for 25-35%; Organic zirconium salts account for 30-40%; Polyvinyl butyral accounts for 8-15%; Antioxidant 1010 accounts for 5-10%, The balance was xylene.

2. A method for preparing a thick copper packaged circuit board resistant to high salt spray corrosion, for preparing the thick copper packaged circuit board resistant to high salt spray corrosion according to claim 1, characterized in that: The following steps are involved: S1: premixing BT resin and glass fiber cloth in a predetermined ratio, and adopting hot melt impregnation and pressing process to prepare a glass fiber-BT composite core layer for standby use; S2: preparing a fluorine-modified polyimide encapsulation layer material by sequentially adding a fluorinated polyimide resin, nano-alumina, polytetrafluoroethylene powder, and a silane coupling agent into a mixed solvent of toluene and NMP, and uniformly dispersing them under stirring to form an encapsulation coating solution for use; S3: preparing a surface anti-corrosion composite coating material, adding a silane coupling agent, an organic zirconium salt, polyvinyl butyral and an antioxidant 1010 to a xylene solvent in sequence, and stirring evenly to form an anti-corrosion composite coating for later use; S4: The roughened thick copper foil is laminated to the glass fiber-BT composite core layer prepared in S1 by hot pressing to obtain a thick copper conductor; S5: evenly applying the fluorine-modified polyimide encapsulation coating liquid prepared in S2 to the surface of the thick copper conductor layer, drying and thermally curing to form an encapsulation layer; S6: applying the anti-corrosion coating prepared in S3 to the surface of the encapsulation layer in sequence by spraying to form a composite anti-corrosion coating; S7: The circuit board with each layer of construction is solidified and hot-pressed at a preset temperature to obtain a finished thick copper packaged circuit board.

3. The method for preparing a thick copper packaged circuit board resistant to high salt spray corrosion according to claim 2, characterized in that: Said S1 specifically includes: S11: evenly spreading BT resin on the surface of the spread glass fiber cloth to form a resin covering layer, wherein the mass ratio of the BT resin powder to the glass fiber cloth is 6:4; S12: feeding the resin-covered glass fiber cloth into a hot melt impregnation device and heating it at a temperature of 180°C to 200°C, so that the BT resin melts and penetrates into the gaps between the fibers under heating, forming a semi-cured sheet in a fully resin-impregnated state; S13: hot pressing and curing the semi-cured sheet in a pressing device under the conditions of a pressure of 0.8 to 1.2 MPa, a temperature of 200° C. to 220° C., and a time of 90 to 120 seconds to obtain a glass fiber-BT composite core layer with a thickness of 0.2 mm to 0.4 mm.

4. The method for preparing a thick copper packaged circuit board resistant to high salt spray corrosion according to claim 2, characterized in that: The S2 specifically includes: S21: In a stirred reactor, toluene and NMP are mixed in a mass ratio of 3:2 to prepare a mixed solvent, and the mixed solvent is heated to 40° C. for later use; S22: adding the fluorinated polyimide resin to the heated solvent, maintaining a stirring rate of 600-800 rpm, and pre-dissolving the resin at a constant temperature for 20-30 minutes to form a preliminary sol state; S23: Add nano-alumina, polytetrafluoroethylene powder and γ-aminopropyltriethoxysilane in sequence, increase the stirring rate to 900-1000 rpm, and continue dispersing at 60°C for 50-60 minutes to form a homogeneous suspension system; S24: After the dispersion is completed, the mixture is allowed to stand for degassing for 30 minutes to obtain a fluorine-modified polyimide encapsulation coating liquid.

5. The method for preparing a thick copper packaged circuit board resistant to high salt spray corrosion according to claim 2, characterized in that: The S3 specifically includes: S31: Add xylene solvent to the stirred reaction vessel, control the initial temperature to 25°C-30°C, and set the stirring rate to 500-600 rpm; S32: Add silane coupling agent and organic zirconium salt in sequence, and continue stirring for 20-30 minutes; S33: Then, polyvinyl butyral and antioxidant 1010 were added, and the stirring rate was increased to 800-900 rpm. Stirring was continued at 40° C.-50° C. for 30-40 minutes to form a composite solution; S34: Filter the composite solution through 100 meshes to remove undissolved particles to obtain an anti-corrosion composite coating.

6. The method for preparing a thick copper packaged circuit board resistant to high salt spray corrosion according to claim 2, characterized in that: The S4 specifically includes: S41: roughening an electrolytic copper foil having a thickness of 200-400 μm using a chemical micro-etching solution, controlling the rough etching time to be 30-60 seconds, and achieving a surface roughness Ra of 0.8-1.5 μm after the treatment; S42: Cleaning the roughened copper foil surface with deionized water and performing hot air drying at 80° C. to 100° C. to remove residual liquid and moisture on the surface; S43: The glass fiber-BT composite core layer prepared in S1 is laminated with the roughened copper foil in a hot press. The pressing temperature is set to 190°C-210°C, the pressure is set to 1.0-1.5 MPa, and the holding time is set to 120-180 seconds. After cooling to room temperature, a thick copper conductor structure with a stable combination of the copper foil and the core layer is formed.

7. The method for preparing a thick copper packaged circuit board resistant to high salt spray corrosion according to claim 2, characterized in that: The S5 specifically includes: S51: applying the fluorine-modified polyimide encapsulation coating liquid prepared in S2 to the surface of the thick copper conductor layer through a coating machine, controlling the application speed to be 200-300 mm / s; S52: Send the coated circuit board into a hot air drying oven, set the drying temperature to 80℃-100℃, and the drying time to 5-10 minutes to remove the solvent residue and initially set the coating film; S53: placing the dried sample in a hot press furnace for heat curing treatment, setting the curing temperature to 220° C.-250° C. and the heat preservation time to 30-40 minutes, to form a cured encapsulation layer with a thickness of 15-20 μm.

8. The method for preparing a thick copper packaged circuit board resistant to high salt spray corrosion according to claim 2, characterized in that: The S6 specifically includes: S61: evenly spraying the anti-corrosion composite coating prepared in S3 onto the surface of the fluorine-modified polyimide encapsulation layer, with the nozzle diameter set to 0.3-0.5 mm, the spraying pressure controlled at 0.2-0.3 MPa, the spraying distance set to 150-200 mm, and the entire surface covered in a spiral trajectory to form a first coating layer with an initial film thickness controlled at 4-6 μm; S62: After the first spraying is completed, hot air pre-drying is performed at 70℃-80℃ for 5-8 minutes; S63: Repeat the second spraying process, with the application track staggered with the first, and control the coating thickness to be 3-5 μm. After completion, repeat the drying step of S62 again to form a composite anti-corrosion coating with a final film thickness of 7-11 μm; S64: Place the sprayed circuit board in a 50-60°C environment for curing for 2-3 hours.

9. The method for preparing a thick copper packaged circuit board resistant to high salt spray corrosion according to claim 2, characterized in that: The S7 specifically includes: S71: Place the printed circuit board sprayed in S6 on a constant temperature hot pressing platform, set the initial heating rate to 2-3°C / min, and gradually increase the temperature to 150-160°C; S72: When the temperature stabilizes, apply constant hot pressing, control the pressure at 0.5-0.8 MPa, and maintain the hot pressing time for 30-40 minutes; S73: After the hot pressing is completed, the circuit board is slowly cooled to room temperature without removing the pressure, and the cooling rate is controlled at 1-2°C / min. After the temperature is lower than 40°C, the pressure is released and the board is removed to obtain a finished thick copper packaged circuit board.

Citation Information

Patent Citations

  • Forming method of semi-embedded thick copper fine circuit of flexible packaging substrate

    CN114190002A

  • Polytetrafluoroethylene composite resin and preparation method thereof

    CN120158015A

  • Flexible wiring board with seal part

    JP2017045780A